1996
DOI: 10.1126/science.272.5267.1486
|View full text |Cite
|
Sign up to set email alerts
|

Infection and AIDS in Adult Macaques After Nontraumatic Oral Exposure to Cell-Free SIV

Abstract: Unprotected receptive anal intercourse is a well-recognized risk factor for infection with human immunodeficiency virus-type 1 (HIV-1). Isolated human case reports have implicated HIV-1 transmission by oral-genital exposure. Adult macaques exposed nontraumatically to cell-free simian immunodeficiency virus (SIV) through the oral route became infected and developed acquired immunodeficiency syndrome (AIDS). The minimal virus dose needed to achieve systemic infection after oral exposure was 6000 times lower than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
82
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(90 citation statements)
references
References 54 publications
6
82
2
Order By: Relevance
“…We found that the ratio of the minimal oral dose to the minimal i.v. dose (r min-adult ) was approximately 1,000 (4). In the present neonatal study, the estimated r min-neonate was at least 50,000 (Table 1), a value similar to that obtained when AID 50 values were compared (Table 2).…”
supporting
confidence: 65%
“…We found that the ratio of the minimal oral dose to the minimal i.v. dose (r min-adult ) was approximately 1,000 (4). In the present neonatal study, the estimated r min-neonate was at least 50,000 (Table 1), a value similar to that obtained when AID 50 values were compared (Table 2).…”
supporting
confidence: 65%
“…In a primate model, when the surface of macaque palatine tonsils was exposed atraumatically with cell-free simian immunodeficiency virus (SIV), infected cells were first detected within the reticulated epithelium lining the tonsillar crypts. 15,16 This unique anatomical compartment, the tonsil crypt epithelium, is specialized to participate in antigen sampling and immune surveillance. Structurally, the surface epithelium of the palatine and lingual tonsils is a continuation of the stratified squamous epithelium of the oral mucosa, but the epithelium of the crypts becomes reticulated and highly infiltrated with lymphocytes, which together with dendritic cells and M cells facilitate transepithelial access of antigens.…”
mentioning
confidence: 99%
“…In 1996, Baba et al reported that the simian immunodeficiency virus (SIV), which is related to HIV, was significantly more transmissible to macaque monkeys through the oral route than through the rectal route. 17 The monkeys were infected in the absence of oral lesions; therefore, the authors suggest that the site of entry for the virus was either the stomach or the tonsils. The authors had demonstrated that inhibition of gastric acid, previously presumed to kill the virus, made no difference in transmission rates.…”
Section: Review Of the Literaturementioning
confidence: 99%